Pengembangan Multimedia Interaktif Mobile Learning Pengurusan Jenazah - Muhamad Tri Panunggal Aprianto; Saida Ulfa; Arafah Husna (Jurnal Kajian Teknologi Pendidikan, 2021)
Abstract: Technology is expected to be used as one way to advance education in Indonesia. The purpose of developing interactive multimedia mobile learning body management is to produce products, which are attractive, interactive, growing interest and the learning spirit of students, learning without barriers and can play a role in the flexibility of learning more personalized and worthy of use. The Mobile learning interactive Multimedia product contains both dialogue, text, audio, animated video and images. The research methods used are research and development and on this development model used in the form of Model Lee & Owens. This research uses models from multimedia development according to Lee & Owens with three stages of completion, namely assessment/analysis, design and development. Development Results Interactive Multimedia Mobile Learning Body Management is a positive response and worth using.